Wavelength Reuse for Short-Reach Optical Access Network Utilizing MDM - Yuanxiang Chen; Juhao Li; Jinglong Zhu; Paikun Zhu; Yu Tian; Huangfa Peng; Yongchi Xu; Jingbiao Chen; Yongqi He; Zhangyuan Chen (IEEE Photonics Journal)
Wavelength reuse has been proposed as an effective solution to realize colorless optical network units (ONUs) for next-generation passive optical network with simplified maintenance and reduced cost. In this paper, we propose a wavelength reused mode-division-multiplexing (MDM) scheme for bidirectional short-reach optical access network with low mode-crosstalk multiplexer/demultiplexer (MUX/DEMUX) and few-mode fiber (FMF). In downstream (DS) transmission, one of the spatial modes in FMF is used to transmit optical carriers, while the others are used as DS signal channels. In upstream (US) transmission, the carrier is split to all the ONUs for US remodulation. By utilizing low mode-crosstalk mode MUX/DEMUX and FMF, the carrier and each signal channel can be effectively separated. Compared with other wavelength reused schemes in which the DS and US transmission are modulated in orthogonal dimension, the signal qualities on two transmission directions are independent in the proposed scheme, and symmetrical bidirectional transmission without residual remodulation crosstalk can be achieved. What is more, to reduce bidirectional Rayleigh backscattering noise, we propose to use different optical sidebands for DS and US transmission. With the proposed scheme, we experimentally demonstrate symmetrical bidirectional 2 × 12.5-Gb/s quadrature phase-shift keying (QPSK) orthogonal-frequency-division-multiplexing (OFDM) intensity-modulation and direct-detection transmission over 11.5-km four-mode FMF. With Rayleigh backscattering noise mitigation, a Q-factor improvement of 2 dB is achieved for the US signal at the DS signal-to-carrier power ratio of −27 dB.